The Relevance of the Household Production Function and Its Implications for the Allocation of Time - Pollak, Robert A.; Wachter, Michael L. (Journal of Political Economy, 1975)
Your use of the JSTOR archive indicates your acceptance of JSTOR's Terms and Conditions of Use, available at